Identification, classification and quantification of microplastics in road dust and stormwater. (July 2022) - Monira, Sirajum; Roychand, Rajeev; Bhuiyan, Muhammed A.; Hai, Faisal I.; Pramanik, Biplob Kumar
Abstract: Microplastics (MP) have become a major emerging class of pollutants representing significant eco-toxicological risks for ecosystems and marine environments. The aim of this study was to identify, classify and quantify MP present in both road dust and stormwater samples. A significantly higher level of MPs within road dust samples was detected from industrial area (1130 particles/kg of dust) than from residential area (520 particles/kg of dust), while stormwater samples from industrial and residential sites yielded 26 particles/L and 17 particles/L, respectively. Fiber-like shape accounted for 53% and 74% in road dust and stormwater samples, respectively. The main polymeric materials collected for both road dust and stormwater samples were, in order of occurrence (i) low-density polyethylene, (ii) high-density polyethylene, (iii) polypropylene, (iv) polyethylene terephthalate, (v) polystyrene, (vi) polyester and (vii) poly (amide). Most of the MP had an average maximum dimension smaller than 2 mm for both road dust and stormwater samples. The results from this study demonstrates that road dust is a significant contributor to MP pollution through direct polymeric materials wear off and transfer through stormwater, which eventually will end up in open water ways and broader ecological niches. Graphical abstract: Image 1 Highlights: Number of MPs was found higher in industrial area than residential area. Fibers were dominant in both road dust (53%) and stormwater (74%). LDPE, HDPE, PP, nylon, polyester, PET and PS were detected as major polymers. Polyester was supreme with 33% in road dust and 46% PET in stormwater samples.